2012
DOI: 10.1016/j.toxlet.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hydroquinone exposure causes tracheal hyperresponsiveness due to TNF secretion by epithelial cells

Abstract: Hydroquinone (HQ) is the main oxidative substance in cigarette smoke and a toxic product of benzene biotransformation. Although the respiratory tract is an inlet pathway of HQ exposure, its effect on airway muscle responsiveness has not been assessed. We thus investigated the effects of low dose in vivo HQ-exposure on tracheal responsiveness to a muscarinic receptor agonist. Male Swiss mice were exposed to aerosolised 5% ethanol/saline solution (HQ vehicle; control) or 0.04 ppm HQ (1h/day for 5 days) and trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…The source of TNFα and TGFβ may be immune cells and epithelial cells (Salib et al, 2005;Mayer et al, 2008;Halwani et al, 2011;Shimada et al, 2012;Gillette et al, 2013). Although the mechanism by which stress increases the transcription of the α-chain and pIgR genes is unknown, the increase observed in the expression of these genes could be a result of the higher expression of the genes for TGFβ.…”
Section: Effects Of Acute Stress On Nasal Iga Levelsmentioning
confidence: 99%
“…The source of TNFα and TGFβ may be immune cells and epithelial cells (Salib et al, 2005;Mayer et al, 2008;Halwani et al, 2011;Shimada et al, 2012;Gillette et al, 2013). Although the mechanism by which stress increases the transcription of the α-chain and pIgR genes is unknown, the increase observed in the expression of these genes could be a result of the higher expression of the genes for TGFβ.…”
Section: Effects Of Acute Stress On Nasal Iga Levelsmentioning
confidence: 99%
“…We observed that the exposure to CS led to increased inflammatory cell infiltrates after the second, fourth, and fifth days of exposure to CS. Shimada et al (2012) demonstrated that short-term exposure to hydroquinone, a substance in CS, increased the influx of inflammatory cells into the tracheal tissue of Swiss mice. In the current study, there was an increase in the number of inflammatory cells in the DM on the third day of exposure to CS, corroborating our previous results, showing that exposure to formaldehyde for 5 days caused an inflammatory response in both trachea and DM in Fischer male rats (Kurgat et al, 2016; Lima et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Another essential organ for ventilation is the diaphragm muscle (DM), which is a skeletal striated muscle that separates the chest and abdominal cavities and can inflate and deflate the lungs, resulting in inspiratory and expiratory movements. Compounds in CS can cause hyperresponsiveness of the airways, leading to inflammation and impaired function of the respiratory system (Merrell and Kardon, 2013; Shimada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dra. Sandra Farsky (Faculdade de Ciências Farmacêuticas (FCF-USP)), colaboradora deste projeto, tem demonstrado que animais expostos à HQ, por aerossol, apresentam uma menor resposta inflamatória de origem alérgica (Macedo et al, 2006;Macedo et al, 2007) e inata (Ribeiro et al, 2011;Shimada et al, 2012a;Shimada et al, 2012b), além do agravamento da artrite reumatóide induzida por colágeno em ratos (Heulany et al, comunicação pessoal).…”
Section: Fontes De Exposição à Hidroquinonaunclassified
“…Entretanto, em relação à infecção pelo vírus da Dengue, a proteção contra um sorotipo específico, não necessariamente conferirá proteção contra um sorotipo diferente (Crill et al, 2009). (Macedo et al, 2006;Macedo et al, 2007;Ribeiro et al, 2011;Shimada et al, 2012a;Shimada et al, 2012b).…”
Section: Fontes De Exposição à Hidroquinonaunclassified